PERCEIVED SECURITY TERHADAP CONTINUANCE INTENTION TO USE MELALUI PERCEIVED USEFULNESS PADA ZOOM - Ghozihan, Nadyah Nur; Nugroho, Dian Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the effect of perceived security on continuance intention to use through perceived usefulness in using the Zoom application in Malang. The influence studied is the direct and indirect effect of the variables. This study used a sample of 110 respondents with purposive sampling as a sampling technique. The sample criteria are active students of the University of Brawijaya undergraduate study program who are more than 18 years old and have used the Zoom application. The test equipment used is the research instrument test, sobel test, and path analysis. From the test results, it can be concluded that perceived security has a significant direct effect on perceived usefulness. Perceived security also has a significant direct effect on continuance intention to use. Perceived usefulness also has a significant direct effect on continuance intention to use. And the test results show that perceived security has an indirect effect on continuance intention to use which is mediated by perceived usefulness.